Differential Expression of PAI-RBP1, C1orf142, and COTL1 in Non–Small Cell Lung Cancer Cell Lines With Different Tumor Metastatic Potential. (1st April 2012) - Sun, Wenjing; Guo, Changlong; Meng, Xiangning; Yu, Yang; Jin, Yan; Tong, Dandan; Geng, Jingshu; Huang, Qi; Qi, Jiping; Liu, An; Guan, Rongwei; Xu, Lidan; et al.
Abstract : Human non–small cell lung cancer (NSCLC) is one of the most common malignancies in the modern world. Its recurrence is mainly due to its ability to invade and metastasize. However, the precise mechanism for tumor development and metastasis is still not fully understood. To shed light on the development of lung cancer, the human giant cell lung carcinoma cell lines 95D with high metastatic potential and 95C with low metastatic potential were selected in this study. The 2 cell lines originated from the same parental cell and share a similar genetic background. In the current study, we identified 3 differentially expressed proteins in 95C and 95D cell lines, namely, PAI-RBP1, C1orf142, and COTL1, by using 2-dimensional electrophoresis proteomics analysis. We found that PAI-RBP1 and C1orf142 expression levels were higher in 95D than in 95C cells, whereas COTL1 expression level was lower in 95D when compared to 95C cells. We also confirmed these results by reverse transcription–polymerase chain reaction and immunoblotting analyses. The messenger RNA and protein levels of PAI-RBP1 and C1orf142 were much higher in 95D than in 95C cells, and COTL1 expression level was lower in 95D than in 95C cells. The PAI-RBP1 expression was assessed by immunohistochemistry in 70 NSCLC and 7 normal lung tissue samples from patients. PAI-RBP1 expression level was higher in tumor tissues (positive staining in 87.1% of cases [61/70]) than in normal tissues (positive staining in 14.3% of cases [1/7]). In conclusion, by studying protein expression in NSCLC cell lines with high and low metastasis as well as in human lung cancer tissues, we have identified 3 proteins, namely, PAI-RBP1, C1orf142, and COTL1, which were differentially expressed in NSCLC cell lines with different metastatic potential. In addition, we also found that PAI-RBP1 might contribute to NSCLC development.